2015
DOI: 10.1159/000441720
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a Tissue-Engineered Neo-Bile Duct in Domestic Pigs

Abstract: Background: Extrahepatic bile duct injuries remain severe complications during cholecystectomies and often require reconstruction by bilioenteric anastomosis (i.e., hepaticojejunostomy), which comes with further long-term complications (e.g., recurring ascending cholangitis, secondary biliary cirrhosis). In the case of inherent extrahepatic biliary atresia or during liver transplant, artificial or engineered bile ducts could allow novel surgical strategies without the need for hepaticojejunostomy. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Cheng et al (2016) successfully transplanted a decellularized ureter, splinted by a silicone stent or a T‐tube, in guinea pigs. In parallel, Struecker et al (2016) transplanted porcine abdominal aorta, which was recellularized with autologous cholangiocytes, in a porcine model. However, ureter or aorta ECM does not resemble the architecture of human EBD as these structures are lacking the complex PBG architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al (2016) successfully transplanted a decellularized ureter, splinted by a silicone stent or a T‐tube, in guinea pigs. In parallel, Struecker et al (2016) transplanted porcine abdominal aorta, which was recellularized with autologous cholangiocytes, in a porcine model. However, ureter or aorta ECM does not resemble the architecture of human EBD as these structures are lacking the complex PBG architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maintaining viability of cholangiocytes after transplantation would require the development of a blood vessel network. Struecker et al (2016) showed feasibility of transplanting a bile duct construct solely with cholangiocytes in a large animal model without forming blood vessels (before transplantation). This could suggest that a preformed blood vessel network is not required, as formation of blood vessel after implantation appeared to be adequate.…”
Section: Discussionmentioning
confidence: 99%
“…On the tissue repair side, the technology for engineering endodermal tissues in vitro on decellularized matrices has improved during the last few years [103] , and may be applied to engineering bile ducts. Engineered neo-bile ducts were successfully transplanted into pigs and well tolerated [104] . Recently, Sampaziodis et al., (2021) showed that extrahepatic organoids could successfully be transplanted to repair intrahepatic biliary ducts in human livers ex vivo and organoid-derived cells regenerated 40-85% of the injected ducts [28] .…”
Section: Towards Therapy Development For Biliary Atresiamentioning
confidence: 99%
“…Many tissue engineering protocols rely on multi-day culture timelines and numerous reagents to evaluate products [34][35][36][37]. Reactors housing organs or vessels require calibrated perfusion [38][39][40]. Scale-up and product transport remain challenges for tissue engineered products [41][42][43].…”
Section: Discussionmentioning
confidence: 99%